Kajian Produksi Tapioka pada Industri Kecil di Kabupaten Manokwari Berbasis Kesetimbangan Bahan (Studi Kasus pada IKM Kharisma) - Aman, Wilson Palelingan (Fakultas Teknologi Pertanian, Universitas Papua, Manokwari, 2024)
The cassava processing industry in Manokwari has been limited to utilizing tapioca products for food purposes. While some of the cassava derivative products produced by the tapioca industry have the potential as non-food products such as feed and bioenergy. To determine the feasibility of utilizing the products of the tapioca industry, a quantitative overview is needed through material mass balance analysis. A quantitative overview of the tapioca industry process in Manokwari is not yet available. Mass balance analysis can provide an overview of material inputs and outputs in the tapioca industry production system. This study aims to obtain a quantitative picture through mass balance analysis of materials in the tapioca industry in Manokwari. This research was conducted using the observation method in the tapioca industry of IKM Kharisma SP 5 Manokwari. The results of the study provide a quantitative description of the material flow process during the production process. From 1778 kg of cassava, 1388 tubers (78.17%) and 388 kg of skin waste (21.83%) were obtained. The amount of wet starch produced from these tubers was 550 kg (40.28%), while the waste in the form of onggok was 448 kg (49.92%). The amount of dry starch (tapioca) produced was 329 kg or 23.70%. Based on the results of the study, it can be concluded that mass balance analysis can describe the quantitative process of each stage and the overall tapioca production process at IKM Kharisma in Manokwari.